2022
DOI: 10.3389/fnins.2022.751489
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Inhibition of Plppr5 Aggravates Hypoxic-Ischemie-Induced Cortical Damage and Excitotoxic Phenotype

Abstract: Hypoxia-ischemia (HI) is the most common acute brain threat in neonates and a leading cause of neurodevelopmental impairment. Exploring the new molecular mechanism of HI brain injury has important clinical translational significance for the next clinical intervention research. Lipid phosphatase-related proteins (PLPPRs) are regulators of mitochondrial membrane integrity and energy metabolism. We recently found that Plppr5 knockout exacerbated HI impairment in some aspects and partially attenuated the neuroprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Up till now, large amounts of studies have indicated that treatment with melatonin before and after OGD can exert neuroprotective effects in CNS cells. Detailed characteristics of included studies are shown in Table 1 ( Vlkolinsky and Stolc, 1999 ; Pei and Cheung, 2003 ; Andrabi et al, 2004 ; Uchida et al, 2004 ; Duan et al, 2006 ; Gasparova, Stolc, and Snirc, 2006 ; Han et al, 2006 ; Wang et al, 2009 ; Guo et al, 2010 ; Tai et al, 2011 ; Parada et al, 2014 ; Buendia et al, 2015 ; Huang et al, 2015 ; Patino et al, 2016 ; Suofu et al, 2017 ; Carloni et al, 2018 ; Lin et al, 2018 ; Azedi et al, 2019 ; Beker et al, 2019 ; Liu, Ran, et al, 2019 ; Wei et al, 2019 ; Xing et al, 2019 ; Xiang et al, 2020 ; Yang, Zang, et al, 2020 ; Zhi et al, 2020 ; Liu, Cao, Gao, Li, Xia, et al, 2021 ; Liu, Cao, Gao, Li, Zeng, et al, 2021 ; Nasoni et al, 2021 ; Ran et al, 2021 ; Luchetti et al, 2022 ; Sun et al, 2022 ; Su et al, 2023 ). Lin et al reported that exposure of cultured neurons obtained from the cerebral cortices of Sprague-Dawley rats to 30 min of OGD and 1, 2, 4, and 24 h of reoxygenation caused the increase of cell apoptosis, while pretreatment with melatonin (10–500 µM) before OGD/R for 30 min could promote the survival of neurons (Y.W.…”
Section: Protective Effects Of Melatonin In Experimental I/r Injury M...mentioning
confidence: 99%
“…Up till now, large amounts of studies have indicated that treatment with melatonin before and after OGD can exert neuroprotective effects in CNS cells. Detailed characteristics of included studies are shown in Table 1 ( Vlkolinsky and Stolc, 1999 ; Pei and Cheung, 2003 ; Andrabi et al, 2004 ; Uchida et al, 2004 ; Duan et al, 2006 ; Gasparova, Stolc, and Snirc, 2006 ; Han et al, 2006 ; Wang et al, 2009 ; Guo et al, 2010 ; Tai et al, 2011 ; Parada et al, 2014 ; Buendia et al, 2015 ; Huang et al, 2015 ; Patino et al, 2016 ; Suofu et al, 2017 ; Carloni et al, 2018 ; Lin et al, 2018 ; Azedi et al, 2019 ; Beker et al, 2019 ; Liu, Ran, et al, 2019 ; Wei et al, 2019 ; Xing et al, 2019 ; Xiang et al, 2020 ; Yang, Zang, et al, 2020 ; Zhi et al, 2020 ; Liu, Cao, Gao, Li, Xia, et al, 2021 ; Liu, Cao, Gao, Li, Zeng, et al, 2021 ; Nasoni et al, 2021 ; Ran et al, 2021 ; Luchetti et al, 2022 ; Sun et al, 2022 ; Su et al, 2023 ). Lin et al reported that exposure of cultured neurons obtained from the cerebral cortices of Sprague-Dawley rats to 30 min of OGD and 1, 2, 4, and 24 h of reoxygenation caused the increase of cell apoptosis, while pretreatment with melatonin (10–500 µM) before OGD/R for 30 min could promote the survival of neurons (Y.W.…”
Section: Protective Effects Of Melatonin In Experimental I/r Injury M...mentioning
confidence: 99%
“…Whether this function is unique for PLPPR4 and whether it depends on LPA and LPARs remains to be studied. However, recent studies have suggested aggravated phenotypes upon hypoxia/ischemia insults and drug-induced seizures in PLPPR5 KO mice, potentially due to PLPPR5-dependent neuron survival ( Sun et al, 2021 , 2022a ; Wang et al, 2021 ).…”
Section: Phospholipid Phosphatase-related Proteins In Developmental G...mentioning
confidence: 99%